Emergence and control of linezolid-resistant Staphylococcus epidermidis in an ICU of a German hospital. (9th February 2018) - Weßels, Christina; Strommenger, Birgit; Klare, Ingo; Bender, Jennifer; Messler, Sabine; Mattner, Frauke; Krakau, Michael; Werner, Guido; Layer, Franziska
Abstract: Objectives: To investigate an outbreak of linezolid-resistant Staphylococcus epidermidis (LRSE) in an interdisciplinary ICU, linezolid consumption and infection control measures taken. Methods: Routine surveillance of nosocomial infections revealed colonization and infection with LRSE affecting 14 patients during a 15 month period. LRSE isolates were analysed with respect to their clonal relatedness, antimicrobial susceptibility, the presence of cfr and/or mutations in the 23S rRNA, rplC, rplD and rplV genes. cfr plasmids were characterized by Illumina sequencing. Medical records were reviewed and antibiotic consumption was determined. Results: Molecular typing identified the presence of three different LRSE clusters: PFGE type I/ST168 ( n = 5), PFGE type II/ST5 ( n = 10) and PFGE type III/ST2 ( n = 1). Ten strains harboured the cfr gene; we also detected mutations in the respective ribosomal protein genes. WGS revealed an almost identical 39 kb cfr plasmid obtained from strains of different genetic background (ST2, ST5, ST168) that shows high similarity to the recently published LRSE plasmid p12-02300. Due to an increase in the number of patients treated for infections with MRSA, a significant increase in linezolid usage was noted from January to July 2014 (from 5.55 to 20.41 DDDs/100 patient-days). Conclusions: Here, we report the molecular epidemiology of LRSE in an ICU. Our results suggest the selection of resistant mutants under linezolid treatment as well as the spread of cfr -carrying plasmids. The reduction of linezolid usage and the strengthening of contact precautions proved to be effective infection control measures.